THE ARTIFICIAL INTELLIGENCE (AI) READINESS IN ASEAN COUNTRIES: THE GOVERNMENT POLICIES AND FRAMEWORKS (ASEAN Legal Insights, 2024)
The Fifth Industrial Revolution (5.IR) transforms people’s lives, making strong legal frameworks crucial. This article examines artificial intelligence (AI) readiness in ASEAN countries, specifically Malaysia, Thailand, and Singapore, by focusing on the government policies and frameworks of AI. A doctrinal legal analysis methodology was used to evaluate each country’s legal infrastructure, identifying gaps and suggesting proper solutions. Findings show significant variations in AI readiness. Specifically, Singapore demonstrates leadership in AI preparation through its sophisticated regulatory frameworks, robust data protection laws, and proactive policies. Malaysia shows moderate progress in developing a strategic vision for AI but faces difficulties in enforcing regulations. Thailand has guidelines for AI ethics but lacks legislation and enforcement. The study suggests several strategies to improve the readiness of these countries for AI. They should develop comprehensive AI Acts, establish regulatory sandboxes, and form AI ethics committees. Creating AI innovation hubs would support startups with resources and training. International collaboration on AI research and standards should be promoted through global partnerships and forums, cross-border initiatives, exchange programmes, and shared technology infrastructure to foster effective, flexible policies and boost public confidence in AI technologies.